Межкультурная коммуникативная компетенция в про-цессе профессиональной подготовки студентов - Ниязбаева, Н.Н.; Абишева, С.К. (My University, 2013)
This article deals with the urgency of the cultural assignment in teaching foreign languages. The theoretical problems disclosing the links between a language and culture are treated in this article.